Evaluation of the spatial and temporal distribution of ‘Candidatus Liberibacter africanus’ in citrus host plants - Goodchild, Shannon (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.